Pengembangan Aplikasi Modul Pembelajaran Berbasis Android pada Mata Pelajaran Administrasi Sistem Jaringan Untuk Siswa XI TKJ SMK Kartika 1-2 Padang - Rahmadani, Futri; Menrisal, Menrisal; Astri Indah Juwita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This is study aims to determine the Effectiveness of Android-Based Learning Module Application Design in the Network System Administration Subject for XI TKJ Students at SMK Kartika 1-2 Padang in the 2022/2023 Academic Year. This research uses the development method (Research & Development). The research subjects were 43 people. The research model used is the development research model (ADDIE), with the design development steps as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the overall effectiveness test assessment of the effectiveness of the Android-Based Learning Module in the subject of Class XI Network System Administration TKJ SMK Kartika 1-2 Padang amounted to 94.62% so that the level of effectiveness can be interpreted very well used. In conclusion, based on the assessment along with expert input as well as the results of field trials the Android-Based Learning Module as a learning medium has been tested for feasibility, superiority, and can be used in the learning process in the Network Systems Administration subject class XI TKJ SMK Kartika 1-2 Padang.